2021
DOI: 10.12669/pjms.38.1.4645
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID Pandemic and Hybrid teaching on Final year MBBS students’ End of clerkship Exam performance

Abstract: Background & Objectives: The novel coronavirus (SAR-CoV-2) pandemic has revolutionized medical education worldwide. Most medical schools have adopted the online teaching and assessments. Students attending modified clerkships and assessments under the stress of the pandemic, perform and score differently when compared to normal clerkships. We aimed to identify the impact of COVID-19 on final year MBBS students’ EOC (End of Clerkship) examination by comparing them with their scores prior to the COVID and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…The findings indicated that the pandemic did not exert a significant influence on the overall performance of the senior year students. These findings support our assertion that students can study effectively even without direct supervision and meet their deadlines (Aaraj, Farooqi, Saeed, and Khan, 2022).…”
Section: Discussionsupporting
confidence: 88%
“…The findings indicated that the pandemic did not exert a significant influence on the overall performance of the senior year students. These findings support our assertion that students can study effectively even without direct supervision and meet their deadlines (Aaraj, Farooqi, Saeed, and Khan, 2022).…”
Section: Discussionsupporting
confidence: 88%
“…A longer offline learning experience decreased the level of anxiety and stress among the medical students, as there were still more achievable clinical skills than those obtained with full online learning methods [ 55 , 56 ]. Our finding was also affected by the participants as our study sample was predominated by preclinical than clinical students, implying that preclinical students still did not understand the importance of offline classes compared with clinical students who require more offline clinical skill development rather than just discussing it online and will soon become professional medical health teams in the field [ 56 58 ]. Additionally, hybrid learning methods were likely to improve self-directed learning of the students as they had more time to learn medical skills and theory [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our finding was also affected by the participants as our study sample was predominated by preclinical than clinical students, implying that preclinical students still did not understand the importance of offline classes compared with clinical students who require more offline clinical skill development rather than just discussing it online and will soon become professional medical health teams in the field [ 56 58 ]. Additionally, hybrid learning methods were likely to improve self-directed learning of the students as they had more time to learn medical skills and theory [ 58 ]. Consistent with our findings, a previous study also reported that students with lower GPAs were more likely to be depressed [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although COVID-19 policies are designed and deployed for the safety and well-being of people; such policies often create disputes and dissent. A large number of people demonstrate an unwillingness to follow such precautions, especially wearing the facemask [ 17 , 18 ]. People think that wearing a face mask is difficult and may lead to additional respiratory complications if used for a longer period.…”
Section: Introductionmentioning
confidence: 99%